Analisis Perbandingan Blockchain Publik Dan Privat: Keuntungan Dan Tantangan Dalam Sektor Bisnis - Rico Wijaya Dewantoro; Celine Chrysia; Cherry Piya Vagga (PT. Hasba Edukasi Mandiri, 2025)
Blockchain technology has emerged as a significant innovation across various business sectors, offering transparency, security, and operational efficiency. Blockchain is divided into two main categories public and private each with its own advantages and challenges. Public blockchains, such as Bitcoin and Ethereum, enable full decentralization, enhance transparency, and reduce the need for intermediaries. However, they often face scalability issues and high transaction costs. In contrast, private blockchains offer greater control over data and network access, making them more suitable for enterprises that require efficiency and regulatory compliance, though they come with a higher risk of centralization. This study employs the Systematic Literature Review (SLR) method to analyze and compare both types of blockchain in a business context. By reviewing 20 relevant scholarly publications, this research identifies key factors influencing blockchain adoption, including technological readiness, regulatory frameworks, and stakeholder awareness. The findings indicate that a hybrid model combining public and private blockchains is increasingly being adopted to optimize the benefits of both systems. This study is expected to serve as a reference for academics, practitioners, and policymakers in formulating optimal blockchain adoption strategies within the business sector. It also provides insights into the challenges of blockchain implementation and the potential for integration with other technologies in the future.